Evaluation of Pancasila Student Profile Strengthening Project Implementation in Elementary School Grade 1 Using the CIPP Model - Christanti, Margareta Sania Octa; Kusuma, Dani (Journal of Innovation and Research in Primary Education, 2025)
The Pancasila Student Profile Strengthening Project (P5) represents a significant innovation in the Merdeka Curriculum designed to develop six character dimensions in students. Despite various studies conducted, comprehensive evaluation of P5 implementation in Phase A elementary schools remains limited. This study employed an evaluation research design with a qualitative descriptive approach to evaluate P5 Program implementation in Grade 1 at SD Negeri Tambakboyo 02 using the CIPP (Context, Input, Process, Product) model. Research subjects comprised the school principal, Grade 1 teachers, and Grade 1 students. Data collection utilized triangulation techniques including questionnaires, in-depth interviews, direct observation, and documentation study. Data analysis employed the Miles and Huberman model with validation through source triangulation. Context evaluation demonstrated stakeholders' deep understanding of P5 objectives and program alignment with student characteristics (score 90). Input evaluation indicated thorough planning despite funding limitations (score 77.5). Process evaluation revealed excellent implementation with high flexibility (score 92.5). Product evaluation confirmed objective achievement through comprehensive assessment systems (score 93.3). The P5 program proved effective in providing meaningful learning experiences and developing student character. P5 implementation success depends on the synergy between thorough planning, stakeholder commitment, implementation flexibility, and adaptive capacity to address challenges. The program effectively develops character according to the six dimensions of Pancasila student profile through project-based learning approaches. Enhanced financial support and external collaboration mechanisms are needed to maximize program potential while maintaining implementation flexibility.